Theyyam: When the ‘lower castes’ turn gods and goddesses - Vishnu Varma
An ancient ritualistic Kerala dance form that elevates members of the lower castes to the stature of God, Theyyam is still seen as a warcry against the caste system, and is undergoing a wave of resurgence.